PERANCANGAN MEDIA INTERAKTIF SEBAGAI MEDIA PENGENALAN HURUF HIJAIYAH UNTUK ANAK TK DI JAKARTA - Bagus Arya Pamungkas; Ateng Setiawan; R. Widyo Wibisono (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2025)
Designing an Interactive Website as a Media for Recognizing Hijaiyah Letters for Wibowo Kindergarten Children is an innovative project that aims to increase Kindergarten children's understanding and interest in Hijaiyah letters. By utilizing web technology and graphic design, this project creates a fun and interactive learning environment. Through an interactive media concept, this website brings an interesting learning experience for children in understanding the form, pronunciation and values of the Hijaiyah letters. The design process involved analyzing children's needs, developing content, and testing user responses. The result is a website that not only supports learning Hijaiyah letters but also stimulates children's creativity and interest in the learning process.